Exploring culture conditions of the fungus Ganoderma curtisii for the production of enzymes with lignocellulosic activity - Salas-Cuidad, Daniela (2024)
Certain white rot fungi, such as Ganoderma sp., are capable of secreting ligninases, such as manganese peroxidases and laccases. These enzymes have a high economic value due to their potential for the degradation of agroindustrial waste, such as waste from the pineapple activity, which has serious negative environmental impacts in Costa Rica, and the need to integrate these wastes into products with greater added value has been highlighted. The objective of this research was to determine the optimal conditions of a liquid fermentation for the production of enzymes from the fungus Ganoderma curtsii with the potential for lignocellulosic degradation. To obtain the greatest enzymatic activity, the use of a medium low in nutrients, with an acidic pH, in the absence of pineapple fibers, and at least 12 days of incubation was required. The results showed that it was possible to use agricultural waste, specifically focused on the integration of stubble from the pineapple activity in Costa Rica, into a circular economy process.